Blood Donors with Different Types of Human Constitution Demonstrate Different Level of Cytokines - Ochirchuulgan, Bayarsaikhan; Soodoi, Chimedtseren; Sevjid, Badamjav; Dalkh, Tserendagva; Damba, Tsend-Ayush; Sandag, Tsogtsaikhan (Central Asian Journal of Medical Sciences, 2018)
Objective: This study was aimed to determine possible relationship between the types of human constitution used in Mongolian traditional medicine and certain types of immune response in healthy blood donors. Materials and methods: Ninety-three blood donors were enrolled in this cross-sectional study. The type of human constitution was determined using the method of Sachs R (1995) and modifi ed by Batchimeg et al. (2003), in which the titer of cytokines (Human IL-2, IL-6, IL-10, IFNγ and TGFβ) in blood plasma and in supernatant of 12- hour PBMC culture were measured by ELISA. Results: Analysis and comparison of different cytokine titers in different constitution groups produced the following fi ndings: Subjects with Badgan ( Tibetan-badken, or phlegm, or bile) type of constitution had a lower activity of Th2 mediated immune response; subjects with Shar ( Tibetan-mkrispa [kris-pa] or mucus) humour domination had a higher activity of Th2 mediated response; and subjects with Khii humour domination may demonstrate higher activity of Th1 mediated response. Conclusion: Human typology types used in Mongolian traditional medicine are likely related to activity or intensity of certain types of adaptive immune responses and authors see an essential need to continue research in this fi eld of study.